Root growth and dental eruption in modern human deciduous teeth with preliminary observations on great apes. Issue 129 (April 2019) - Mahoney, Patrick
Abstract: Recent studies of dental development have indicated that root growth rates are linked to the eruption of some permanent tooth types in modern humans and Pan troglodytes . Little is known about the potential links between these aspects of dental development in deciduous teeth of any primate species. This histology study calculates the rate at which roots extend in length for human deciduous maxillary teeth and a small sample of deciduous canines and premolars from P. troglodytes and Pongo pygmaeus . Links are sought between root extension rates and previously published data for deciduous tooth emergence in each of these species. Results reported here provide the first evidence that the roots of human deciduous incisors, canines, and premolars extend in length at an accelerated rate as these teeth emerge. Accelerated extension rates in a deciduous canine from Pan coincided with the age that this tooth type emerged in captive chimpanzees. High extension rates in a canine from Pongo preceded emergence age. Preliminary observations indicate that deciduous canine and premolar roots of Pan and Pongo extend in length rapidly when compared to these tooth types from modern human children. This study provides a starting point from which to investigate new links between the incremental development of deciduous roots and tooth emergence in primates.